Forms and Meanings of the Sekujang Oral Tradition in Selingsingan and Simpang Villages, Seluma Regency, Bengkulu Province - Rahmat Wahyuddin; Kasmantoni; Henry Friatary (JPI: Jurnal Pustaka Indonesia, 2024)
Oral traditions constitute an important element of intangible cultural heritage, serving as a medium of cultural transmission, identity formation, and moral education, yet many of these traditions remain underexplored in academic scholarship. This study aimed to analyze the forms and meanings of the Sekujang oral tradition practiced by the Serawai community in Selingsingan and Simpang Villages, North Seluma District, Bengkulu Province. A qualitative descriptive design was employed, using documentation, observation, and in-depth interviews with cultural practitioners and community elders as data collection techniques. The collected pantun texts were transcribed, coded, and thematically analyzed to identify structural features and cultural values embedded in the tradition. The findings revealed that Sekujang is performed through pantun recitations that encompass themes of gratitude, respect, and communal harmony, while also functioning as a vehicle for intergenerational knowledge transfer and social cohesion. The analysis further demonstrated that Sekujang reflects the Serawai people’s worldview and ethical norms, particularly concerning respect for nature, kinship, and spirituality. The novelty of this research lies in its systematic documentation and interpretive analysis of Sekujang, a tradition that has received limited scholarly attention compared to other Indonesian oral performances. These results imply that Sekujang should be integrated into cultural preservation programs and educational initiatives to strengthen cultural identity, promote local wisdom, and support heritage policies at the regional and national levels.